Efeito de valores de reforço informativo de marcas de produto de limpeza automotiva sobre escolhas discretas e desconto temporal: um estudo sobre consumo em mercado especializado - Granja, Isis Juliane Arantes (2023)
At all times we notice consumer behavior occurring and from that, verifying the consumption of specialized (not common) products, important values can be added to the product. Given this, this thesis admits analyzing the consumption of specialized products from the perspective of the Behavioral Perspective Model (BPM), based on the analysis of the relationships between levels of informative reinforcement of consumption. The present study investigated the informative reinforcement levels of 5 (five) brands of acid descaler manufacturers, verification of the temporal discount and the effects of the brand. Under the methodological conditions of the study, the greater magnitude of information reinforcement of the brands FACIGOL2002 and FX4000 was evidenced, with emphasis on the first, which presented the highest iCQ and was the most chosen in the task of choosing brands. The subjective value of both, as well as the other brands, was neatly discounted with the temporal delay of the programmed reinforcing consequence ("clean car")